2002
DOI: 10.1046/j.1439-037x.2002.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution (Texture) of Eroded Soil Material

Abstract: The total quantity of erosional drift on a Stagnic Luvisol on which six tillage methods were used was measured over 5 years of investigation. The texture of the tilled soil and the erosional drift for each trial method was recorded in the same plots. The results obtained suggested that erosional drift was generally richer in silt and clay particles. The standard deviations of coarse sand indicated that approximately the same quantity of coarse sand was found in plot soil and in erosional drift for all tillage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
3
11
0
Order By: Relevance
“…The values of ER SOC were always >1 in our study indicating an enrichment of SOC in the runoff sediment compared with the original soil. This result is confirmed by many researchers (for example, Basic et al. , 2002; Kisic et al.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The values of ER SOC were always >1 in our study indicating an enrichment of SOC in the runoff sediment compared with the original soil. This result is confirmed by many researchers (for example, Basic et al. , 2002; Kisic et al.…”
Section: Discussionsupporting
confidence: 85%
“…, 1999). Numerous studies have shown that long‐term conventional ploughing up and down slope is the least desired tillage method (Basic et al. , 2002; Kisic et al.…”
Section: Discussionmentioning
confidence: 99%
“…Their results were in agreement with the ones of Basic et al (2002) who also found that the eroded sediment had higher silt and clay content compared with the original soil, but no differences for the coarse sand content as compared to the original soil were observed, suggesting a selective transport of finer particles in respect to the original soil.…”
Section: Introductionsupporting
confidence: 91%
“…compaction and/or looseness state; level of aggregation at diff erent land use; consequences of water and wind erosion; drought and water-logging situations). While the preliminary results were published both by Hungarian (Bencsik et al, 2007;Birkás et al, 2002;2006; and Croatian relation (Basic et al, 2002;Jug and Stipesevic, 2006a,b;Kisic et al, 2003;2005;2006;Sabo et al, 2007), in this paper the important facts are only listed. Th e soil consequences of reduced and over-reduced tillage practice are also presented.…”
Section: Methodsmentioning
confidence: 73%
“…In other hand in the tillage practice there were beliefs or bad use in number those have had their time, such as deep and black stubble tillage, cloddy winter ploughing (to catch snow), deep summer ploughing (for soil disinfection by sun), and fi ne-aggregated seedbed for more crops (Birkás, 2006). During the last decades, these traditional goals were forced to change due to the deterioration of soil quality (Basic et al, 2002;Lipiec et al, 2003;Sabo et al, 2006;Farkas et al, 2007). While close correlation is found between soil quality deterioration and climatic harms (e.g.…”
Section: Introductionmentioning
confidence: 99%